The role of distress tolerance in the relationship between cognitive schemas and alcohol problems among college students. (March 2018) - Simons, Raluca M.; Sistad, Rebecca E.; Simons, Jeffrey S.; Hansen, Jamie
Abstract: Introduction: The current study tested the role of distress tolerance in the relationship between three early maladaptive cognitive schemas (Abandonment, Defectiveness/Shame, and Insufficient Self-Control) and alcohol problems among college students (N = 364). Previous research suggests that maladaptive cognitive schemas may be a risk factor for alcohol-related problems. However, the mechanism underlying this association is unclear. One's tolerance for emotional distress may play an important role in understanding the nature of this association. Methods: We tested a structural equation model where distress tolerance was expected to explain or moderate associations between early maladaptive schemas and alcohol outcomes. Results: Results indicated distress tolerance partially mediated the relationships between schemas of Abandonment and Insufficient Self-Control and alcohol problems. Distress tolerance also significantly moderated the relationship between the Defectiveness/Shame schema and alcohol-related problems, reducing the strength of the association. Conclusions: Distress tolerance is a modifiable risk factor and the results of this study support the inclusion of emotional regulation strategies in the prevention and treatment of alcohol problems among young adults. Highlights: Distress tolerance mediates the relationship between Abandonment and Insufficient Control schemas and alcohol problems. Distress tolerance skills buffered the effects of Shame/Defectiveness on alcohol problems. Maladaptive schemas inhibit development of the ability to tolerate negative emotions. Decreasing the rigidity of cognitive schemas and increasing distress tolerance are suggested for intervention.